Enhancing Post Implementation ERP Business Process Maturity Using ISO 9001:2015 and CMMI v3.0: A Case Study of a Manufacturing Company - Bill Petrus Cerullo Gabriel Martin Hutabarat; Eko K. Budiardjo; Kodrat Mahatma (JST (Jurnal Sains dan Teknologi), 2025)
The utilization of Enterprise Resource Planning (ERP) systems in distribution companies is often not fully integrated with business processes and quality management systems, resulting in operational inefficiencies and weak service control. This condition indicates a gap between the potential of ERP as an integrated system and actual practices that still rely on manual processes and informal coordination. This study aims to analyze, evaluate, and formulate improvement recommendations for the maturity of ERP-related business processes during the post-implementation phase through the integration of the CMMI v3.0 model and the ISO 9001:2015 standard. The research employs a mixed-method approach with an evaluative–diagnostic design. The research subjects consisted of six assessors, three validators, and twenty-seven process users directly involved in operational and service activities. Data were collected through semi-structured interviews, questionnaires based on CMMI–ISO indicators, direct observation, and document review as supporting instruments. Data analysis was conducted using evidence-based SCAMPI C appraisal, quantitative descriptive analysis, and thematic qualitative analysis. The findings indicate that most practice areas remain at initial to basic capability levels, with a high dependence on manual work, weak service governance, and direct impacts on SLA compliance and service timeliness. Overall, the study concludes that the integration of CMMI v3.0 and ISO 9001:2015 is effective as a framework for evaluating and improving the maturity of ERP processes in the post-implementation phase. The implications of this study provide practical guidance for organizations to optimize ERP utilization, strengthen process governance, and foster a quality-oriented culture of continuous improvement.